Transformational Leadership of Tuan Guru for Educational Quality Improvement in Islamic Boarding Schools - Samsul Hadi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2026)
Islamic boarding schools (pesantren) have undergone rapid institutional transformation in response to globalization, digitalization, educational accountability, and increasing public expectations of educational quality. Within this context, the leadership of Tuan Guru, who serves simultaneously as a spiritual guide, educational leader, and institutional decision-maker, has become increasingly strategic. Although transformational leadership has been widely examined in educational organizations, empirical studies explaining how the transformational leadership of Tuan Guru contributes to educational quality improvement remain fragmented, particularly in Indonesian Islamic boarding schools. This study aims to explore how Tuan Guru exercises transformational leadership to enhance educational quality through vision development, teacher empowerment, organizational culture, innovation, and stakeholder collaboration. A qualitative multiple-case study design was employed in two established Islamic boarding schools in Indonesia. Data were collected through in-depth interviews, participant observations, and document analysis involving Tuan Guru, school principals, teachers, administrative staff, students, alumni, and community representatives. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing. The findings reveal that transformational leadership is manifested through five interconnected dimensions: visionary leadership grounded in Islamic values, exemplary moral leadership, teacher professional empowerment, adaptive educational innovation, and collaborative governance involving internal and external stakeholders. These leadership practices strengthen institutional governance, teacher professionalism, student achievement, organizational culture, and community trust, thereby supporting sustainable educational quality improvement. This study extends transformational leadership theory by integrating Islamic spiritual leadership values embodied by Tuan Guru with contemporary educational management principles. Practically, the findings offer a strategic framework for Islamic boarding school leaders and policymakers seeking to improve institutional quality while preserving religious identity.